The Effect of Visual Merchandise on Impulse Buying with Emotional Response as an Intervening Variable in the Marketplace - Karina Putri Kaban; Endang Sulistya Rini; Muhammad Anggia Muchtar (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effect of visual merchandise on impulse buying, with emotional response serving as a mediating variable among Shopee marketplace users in Medan City. The research employs a quantitative method using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. Data were collected through questionnaires distributed to 91 active Shopee users. The results indicate that visual merchandise has a positive effect on impulse buying, both directly and indirectly through emotional response. Visual elements such as page design, product image quality, interactive promotions, and digital store navigation are proven to evoke positive emotions, including pleasure, urgency, and self-confidence. These emotional responses strengthen the tendency toward spontaneous purchasing without rational consideration. The findings confirm that emotional experience plays a crucial role in linking visual strategies to consumers’ impulsive buying behavior. Therefore, visual strategies function not only as aesthetic elements but also as effective psychological tools for enhancing consumer engagement and impulsive purchase decisions in the marketplace.